DIPG-47. HISTONE MUTATIONS ENHANCE RAS MEDIATED ERK5 GROWTH SIGNALING IN DIFFUSE MIDLINE GLIOMAS. (4th December 2020) - Stanton, Ann-Catherine; Koncar, Robert; Golbourn, Brian; Dey, Brittany; Agrawal, Nishant; Mack, Stephen; Pollack, Ian; Agnihotri, Sameer
Abstract: Diffuse midline gliomas (DMGs) are incurable brain tumors with an aggressive onset. Apart from irradiation, there are currently no effective therapies available for patients with DMG, who have a median survival time of less than one year. Most DMG cells harbor mutations in genes encoding histone H3 (H3K27M) proteins, resulting in a global reduction of H3K27 trimethylation and activation of oncogenic signaling pathways. Here we show that the H3K27M mutations contribute to RAS pathway signaling, which is augmented by additional RAS activators including PDGFRA. H3K27M mutation led to increased expression of receptor tyrosine kinases (RTK). A RAS pathway functional screen identified ERK5, but not ERK1/2, as a RAS pathway effector important for DMG growth. Suppression of ERK5 decreased DMG cell proliferation and induced apoptosis in vitro and in vivo . In addition, depletion or inhibition of ERK5 significantly increased survival of mice intracranially engrafted with DMG cells. Mechanistically, ERK5 directly stabilized the proto-oncogene MYC at the protein level. Additionally, persistent ERK5 depletion does not result in complete growth inhibition and therefore we set out to determine potential adaptation or resistance mechanisms in response to ERK5 loss. Using RNA-sequencing and Immunoprecipitation (IP) mass spectrometry (IP-MS), we have identified several positive and negative feedbacks involved in ERK5 that are also targetable. These findings identify the H3K27M mutation as an enhancer of RAS activation in DMG with ERK5 and ERK5 regulated networks immediately actionable pathways.